Quadruple Helix Governance As An Effort in Maintaining Food Security Through Islamic Philantrophy - Maulana, Hartomi; Taufani, Mochammad Kharits (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2023)
Food is a basic human need that must be fulfilled at any time and plays many important roles in the life of a nation. A nation's capacity to sustain the economic existence of global dynamics can be attributed to the availability of food that can be obtained by many stakeholders. This paper aims to provide a model of food security through Islamic philanthropy with the Quadruple Helix approach, which is the connection between academia, business, the government and the community,which coordinating well with the other. This paper is a qualitativestudy with the method used was literatureresearchthrough a systematic review approach. The findings of this study provided the result that food self-sufficiency cannot be realized without the role of quality and productivity at the core of food self-sufficiency; thus, the government must take a stand and fully support it. Academics had a significant part in the advancement of technology and effective food processing. The businesses had an equally critical role in supplying financing for industrial growth and creating jobs for the local population. In addition, the government, business and community could assist aid in the development and attainment of food self-sufficiency by creating fuctional food systems that will be possible to implement more suitable policies in the context of achieving food self-sufficiency.Keyword: Food Security, Islamic Philanthrophy, Quadruple Helix, Sustainable Development